Social media marketing between success opportunities and failure risks - HICHOUR, Sara; KOURTEL, Farid (Journal of Human Sciences, 2020)
The phenomenon of using social media has spread significantly and unprecedented at the global level, as these interactive sites succeeded in connecting the whole world and eliminating geographical borders, which required directing more attention from institutions to discuss how to exploit them. Today, the topic of social media marketing has become a major concern for employees and specialists in the field of marketing and  management, it has shifted from being an option for organizations to being a specific necessity in the  light of a highly competitive digital environment, now institutions do not have an option to do marketing through social media or not, but the challenge it faces is how to do it to the fullest.  The success in social media marketing is linked to the efficiency in planning the marketing strategy via social media on one hand and the good implementation of this strategy on the other hand to seize the opportunities available and avoid potential threats and risks.